2015
DOI: 10.17221/8132-cjas
|View full text |Cite
|
Sign up to set email alerts
|

VLDLR gene polymorphism associated with abdominal fat in Gaoyou domestic duck breed

Abstract: VLDLR gene was chosen as a candidate gene infl uencing abdominal fat trait and body weight due to previous studies in human and mouse. Herein, the objectives of this study were to identify genetic polymorphisms of duck VLDLR gene, and to analyze association between combined haplotypes and abdominal fat trait in Gaoyou domestic duck. A total of 207 individuals, including the elite reservation farm Gaoyou duck (FG, n = 50), the newly formed Gaoyou duck (NG, n = 54), the reserve area Gaoyou duck (AG, n = 50), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Gong et al (2014) found significant effects of three polymorphisms within the MSTN gene on body weight of duck in consecutive weeks of age (from 5 to 11 weeks), whereas no effects have been estimated for younger birds. Furthermore, Zhao et al (2015) detected significant associations between the VLDLR gene (for four diplotypes) and body weight at 10 weeks in Gaoyou domestic duck breed. Also, considerable effects of these traits were estimated by Huang et al (2007aHuang et al ( , 2007b.…”
Section: Successful Identification Of Duck Genome Region Determining mentioning
confidence: 85%
“…Gong et al (2014) found significant effects of three polymorphisms within the MSTN gene on body weight of duck in consecutive weeks of age (from 5 to 11 weeks), whereas no effects have been estimated for younger birds. Furthermore, Zhao et al (2015) detected significant associations between the VLDLR gene (for four diplotypes) and body weight at 10 weeks in Gaoyou domestic duck breed. Also, considerable effects of these traits were estimated by Huang et al (2007aHuang et al ( , 2007b.…”
Section: Successful Identification Of Duck Genome Region Determining mentioning
confidence: 85%
“…Many studies have shown associations of VLDLR gene mutations with adiposity and body weight in humans, as previously mentioned in this paper. In a previous study (Zhao et al, 2015), we identified eight SNPs in the homologous domain of VLDLR EGF precursor and showed that there was a significant association between the VLDLR EGF precursor homologous domain and abdominal fat percentage (AFP) in ducks. Similar results were obtained in the present study by analyzing the polymorphism of signal peptide regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that the VLDLR gene may be associated with abdominal fat in duck (Zhao et al, 2015). The objectives of the present study were to detect different polymorphic sites and investigate its association with growth and carcass traits of Gaoyou ducks, and to conduct further research on the possibility of using VLDLR gene as molecular genetic markers for growth and main carcass traits (abdominal fat percentage -AFP, eviscerated weight percentage -EWP).…”
Section: Introductionmentioning
confidence: 97%
“…Качка -один з найбільш економічно важливих видів свійської водоплавної птиці, оскільки слугує джерелом для отримання якісного м'яса, яєць та пір'я (Huang et al, 2013;Purwantini et al, 2013;Zhao et al, 2015;Ren et al, 2017). Близько 70% качок розводять у Китаї (Tunca et al, 2015;Zeng et al, 2016), за даними ФАО (2015) ця країна є лідером з вирощування молодняку качок.…”
Section: вступunclassified